The financial times guide to strategy : how to create, pursue and deliver a winning strategy - Koch, Richard, 1950- (Harlow Pearson Education Limited, 2021)
"The author lays out what quality strategic thinking is, and not in a dry plodding way, but in an exciting, even breathless, way. He points out that business is a war of strategies, where the few good strategies win and laggards fall by the wayside. Resource-based theory, the dominant tautology, provides firm ground on which to build: you will not be successful unless you have some skills or assets that are superior to those of competitors. Whether it is micro-economics, the boundaries of markets, the dynamics of competition or new ideas from biology, mathematics, sociology, psychology, and the science of networks, this book opens the door. Some of the new ideas are well tested and grounded. Other ideas are fertile yet unproven, and others again are frankly snake-oil, complex rearrangements of half-truths to create a fresh but fallacious matrix or methodology that panders to bosses' biases. Some new approaches are highly practical and can be used by any manager; most are not"--
Part 1. Business unit strategy a do-it-yourself guide -- Part 2. Corporate strategy -- Part 3. Strategic thinkers -- Part 4. Strategic ideas - concepts, tools and techniques.
Includes bibliographical references and index.
Keywords: Strategic planning